Determination of optimum tilt angle and orientation for solar collectors based on effective solar heat collection. (1st June 2018) - Lv, Yuexia; Si, Pengfei; Rong, Xiangyang; Yan, Jinyue; Feng, Ya; Zhu, Xiaohong
Highlights: Propose an effective solar heat collection concept to rule out ineffective solar radiation. Apply the optimization model to a solar collector installed in Lhasa. There is about 5° deviation in the optimum orientation between two methods. It is not necessary to adjust the solar collector every month in the studied region. Give correction factors based on total effective solar heat collection. Abstract: Determination of optimum tilt angle and orientation of solar collectors by maximizing the total solar radiation may overestimate the energy production benefits, because a considerable amount of solar radiation is ineffective for practical solar collectors. In this paper, the concept of effective solar heat collection is proposed to rule out the ineffective solar radiation that could not be converted to available energy. Accordingly, an optimized mathematical model is developed and used to determine the optimum tilt angle and orientation of solar collectors installed in Lhasa during the heating season. Compared with the total solar radiation based optimum results, there is a deviation of 5° in the optimum orientations based on the effective solar heat collection. The case study shows that it is not advisable to adjust the optimum tilt angle on a monthly basis because there is no significance change in total solar energy gains in comparison with the case of no such adjustment during the heating season. In addition, the correction factors to achieving the maximum effective solar heat collection are given at different tilt angles and orientations to guide installation of solar collectors in practical engineering applications.